Effects of Timing of Grazing on Arthropod Communities in Semi-Natural Grasslands - Lenoir, Lisette (University of Wisconsin Library, 2010)
Arthropod communities were investigated in two Swedish semi-natural grasslands, each subject to two types of grazing regime: conventional grazing from May to September (continuous grazing) and traditional late management from mid-July (late grazing). Pitfall traps were used to investigate abundance of carabids, spiders, and ants over the grazing season. Ant abundance was also measured by mapping nest density during three successive years. Small spiders, carabids and ants (Myrmica spp.) were more abundant in continuous grazing than in late grazing while larger spiders, carabids, and ants (Formica spp.) were more abundant in late grazing. The overall abundance of carabids was higher in continuous grazing in the early summer but higher in late grazing in the late summer. The switch of preference from continuous to late grazing coincided with the time for larvae hibernating species replacing adult hibernating. We discuss possible explanations for the observed responses in terms of effects of grazing season on a number of habitat variables for example temperature, food resources, structure of vegetation, litter layer, competition, and disturbance.